Pendekatan Tafsir A. Hasan: Analisis Tekstual - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (Al-Irfani: Journal of Al Qur'anic and Tafsir, 2024)
This paper examines the context and method of tafsir by A. Hasan Bandung (1887-1958) based on socio-cultural approaches and the essence of his juristic and hermeneutical views and epistemological postulate, which raises important aspects of socio-legal and ethical reform as its leading voice and proponent. This is highlighted from his interpretative work of Qur’anic exegesis such as Tafsir al-Furqan, Tafsir al-Hidayah, Tafsir Surah Yasin, al-Djawahir, as well as from his column in local magazine and journal such as Himayat al-Islam, Pembela Islam and etcetera. The research is based on qualitative (narrative) methods, using literature/library research, and hermeneutical survey. The finding shows that A. Hasan has outlined an unprecedented method of contextual interpretation of the Qur’an that reflected his rational understanding of the text. This is manifested from his arguments that celebrated the views of classical and contemporary jurist on broad aspects of Islamic law, jurisprudence, speculative theology, philosophy, religious faith, spirituality and Shariah. His interpretation was intrinsically presented in the form of structural kalam based on question and answer that addresses and debates diverse communal issues. It reveals the strength of his views based on ijtihad (independent reasoning) that formulate the entire juristic opinion from broadly authoritative and argumentative construct of maslahah (the common good) dan maqasid syariah (the higher objective of Islamic law).